2017
DOI: 10.1002/pc.24485
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring electrical and thermal properties of polymethyl methacrylate‐carbon nanotubes composites through polyaniline and dodecyl benzene sulphonic acid impregnation

Abstract: A series of composites of polymethyl methacrylate (PMMA) with polyaniline‐multiwalled carbon nanotubes (PANI‐CNTs) as filler I and dodecyl benzene sulphonic acid‐multiwalled carbon nanotubes (DBSA‐CNTs) as filler II are developed by solution mixing method. Composites are characterized for morphological, electrical, and thermal properties to study effect of two different types of additives, PANI, and DBSA. Furthermore, their influence on dispersion of CNTs is also studied. Electrical percolation behavior of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…We have reported in our work, electrical and thermal properties of polymethyl methacrylate CNTs composites with polyaniline-multiwalled carbon nanotubes (PANI-CNTs) as filler. Theoretically calculated percolation threshold was found to be 1.3 wt% [47]. We have also found from research that PANI had lower thermal stability than its composites with MWCNTs and Ag-MWCNTs [48].…”
Section: Polymer\cnt Composites Electrodessupporting
confidence: 50%
“…We have reported in our work, electrical and thermal properties of polymethyl methacrylate CNTs composites with polyaniline-multiwalled carbon nanotubes (PANI-CNTs) as filler. Theoretically calculated percolation threshold was found to be 1.3 wt% [47]. We have also found from research that PANI had lower thermal stability than its composites with MWCNTs and Ag-MWCNTs [48].…”
Section: Polymer\cnt Composites Electrodessupporting
confidence: 50%
“…Low value of electrical percolation is the index of good dispersion [13]. It is also observed that shape of the percolation curve and value of percolation threshold depend strongly upon different factors like temperature, pressure, aspect ratio of fillers, additives used, and method of preparation [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 94%
“…Common concern in this regard is nonhomogenous dispersion of the particles or agglomerate formation of the filler entities. By doping of some additives or modification of the filler to develop the interaction with matrix, aggregation of nanoparticles can be prevented, and it is very necessary for its homogenous dispersion [9][10][11]. Homogeneous dispersion of the filler in the polymer matrix is an essential requirement to impart the electrical and mechanical features of the fillers to the polymer composite [12].…”
Section: Introductionmentioning
confidence: 99%
“…For the development of polymer composites reinforced by nano materials, carbon nanotubes (CNTs) and graphene are found to be excellent fillers [6]. CNTs show remarkable electrical, thermal and mechanical properties along with versatile morphologies [7,8] . These significant properties make them unique among all nanoparticles.…”
Section: Introductionmentioning
confidence: 99%